Surprises party Pianoscope Festival 2008 in Beauvais - Schubert, Franz 1797-1828; Fauré, Gabriel 1845-1924; Brahms, Johannes 1833-1897; Debussy, Claude 1862-1918; Debussy, Claude 1862-1918; Chassy, Guillaume de; Van Heusen, Jimmy 1913-1990; Kosma, Joseph 1905-1969; Castérède, Jacques 1926-2014; Chaminade, Cécile 1857-1944; Lavignac, Albert 1846-1916 (Karl More Productions, 2008)
For the last concert of the Pianoscope Festival in 2008, Brigitte Engerer and his friends pianists have concocted a program of piano works for several hands full of surprises ... Created by Brigitte Engerer, the Pianoscope Festival (Beauvais, France) is still inhabited by the soul of its outstanding founder. An unclassifiable festival, Pianoscope devotes considerable attention to young performers, programs less-known composers and makes the public discover repertoires well off the beaten track. Concerts, masterclasses with the greatest figures of the contemporary piano scene, the festival offers an always renewed programme and attracts an eclectic audience gathered in its common passion for the piano. More than a concert, this is a real show where the crème de la crème of pianists make resonate and quiver their instrument, performing with four, six or eight hands works as classical as eccentric. This wonderful program highlights Schubert, Lavignac, Debussy, Kosma and also Chaminade and ends the Pianoscope Festival that celebrates in 2008 its third anniversary, under the guidance of the incredible pianist Brigitte Engerer. A musical firework not to miss!
Keywords: Piano, Musique de (4 mains); Piano, Musique de; Piano, Musique de (6 mains); Piano, Musique de (8 mains); Piano music; Piano music (4 hands); Piano music (6 hands); Piano music (8 hands); Webcast; Internet videos; Vidéos sur Internet